How Important Is Green Marketing Mix For Consumer? Lesson From The Body Shop - Siti Jahroh, Siti Sarah Chairunnisa, Idqan Fahmi, (Jurnal Manajemen, 2019)
The increasing of consumer needs for cosmetics must be balanced with the care of environmental issues through marketing activities (green marketing). The green marketing concept can be applied in every element of marketing mix comprehensively. The Body Shop is one of the pioneer in cosmetic companies implementing the green marketing mix. The purpose of this study to analyze the effect of green marketing mix towards consumer satisfaction and loyalty. Selected respondents are the consumer who visit the store at least two times within the last six months and above 17 years old. The analysis method used is Structural Equation Modeling (SEM) by SMART PLS software. The result of this study indicate that green marketing mix’s effect towards loyalty through consumer satisfaction is higher than green marketing mix’s effect towards loyalty directly.